A Sequencing Effect of Adding Generative Learning Strategies to Immersive Virtual Reality on Middle School Students' Performance, Intrinsic Motivation, and Self‐Efficacy - Boel, Carl; Rotsaert, Tijs; Valcke, Martin; Schellens, Tammy (Journal of computer assisted learning, 2025)
ABSTRACT Background As immersive virtual reality (IVR) is increasingly being used by teachers worldwide, it becomes pressing to investigate how this technology can foster learning processes. Several authors have pointed to this need, as results on the effectiveness of IVR for learning are still inconclusive. Objectives To address this gap, we first investigated the effect of adding generative learning strategies, that is, teacher‐led instruction and class discussion, to an interactive immersive virtual reality learning experience on learning outcomes, in terms of procedural knowledge, self‐efficacy, and intrinsic motivation. Next, we tested whether the sequencing of the additional classroom activities significantly affected the outcomes. Methods In this value‐added study, we adopted a quasi‐experiment with three groups in a between‐subjects design. The IVR serious game VRkeer, teaching middle school children how to ride a bicycle safely in traffic, was implemented during the study. The IVR‐first group started with the IVR experience and received a more conventional lesson, in which the familiar teacher provided instruction on the topic and engaged students in critical thinking via class discussions using authentic traffic situations as case studies. The class‐first group followed the reverse sequence, and the IVR‐only group served as a control group with two times the IVR experience. 211 middle school students engaged in the experiment and were randomly assigned to one of the three groups, per class in their own classroom, taking ecological validity as a priority. Pre‐ and posttest scores were compared for procedural knowledge, self‐efficacy, and intrinsic motivation (interest/enjoyment and value/usefulness). Results and Conclusions Our results indicate an overall significant increase in all measures, except for intrinsic motivation. Between‐groups results show that the class‐first group outperformed the other groups in terms of knowledge gains and intrinsic motivation, but not in self‐efficacy. Our findings have both theoretical and practical implications, which are discussed alongside study limitations and future research directions.